Media baru: tren berita provokatif ditinjau dari etika komunikasi - Ahmad Sampurna; Farhan Indra; Arya Fandhy (Jurnal Studi Komunikasi, 2024)
This study aims to analyse and explain the urgency of communication ethics in the new media era (new media). This study uses a descriptive qualitative method with a post -positivist approach, where researchers observe and identify the phenomenon of communication ethics in new media (new media) Instagram on the @lambe_turah account naturally. This research data was obtained from the Instagram account @lambe_turah as a source of primary data, as well as from a literature review as secondary data. This research data was analysed through data reduction process, data presentation, and drawing conclusions. The results of this study indicate, with technological developments that allow the spread of fast and broad news on social media platforms, the need to maintain integrity, honesty, and peace in communication becomes more urgent. Communication ethics plays a major role in guiding media actors to verify information carefully, avoid sensationalism, and reduce the risk of provocation to individuals or groups. In dealing with the complexity of new media, enforcement of integrity, honesty, and peace becomes a crucial foundation in ensuring public trust, promoting social harmony, and preventing unwanted conflict escalation. Although the dominance of sensational and provocative news in user interest, ethical principles remain relevant in ensuring that the message distributed is true, useful, and not detrimental. With an emphasis on the principles of communication ethics, we can use new media as a means to strengthen the values of truth, justice, and wisdom in society, as well as facilitate a deeper understanding of various groups.